Plasma Cholesteryl Ester Fatty Acids do not Mediate the Association of Ethnicity with Type 2 Diabetes: Results From the HELIUS Study. Issue 2 (12th December 2017) - Muilwijk, Mirthe; Celis‐Morales, Carlos; Nicolaou, Mary; Snijder, Marieke B.; Gill, Jason M.R.; van Valkengoed, Irene G.M.
Abstract : Scope: Ethnic minority groups have a higher risk of type 2 diabetes (T2D) than the host population. Our aim is to identify whether plasma cholesteryl ester fatty acids (CEFA) mediate the ethnic differences in type 2 diabetes. Methods and results: We included 202 Dutch, 206 South‐Asian Surinamese, 205 African Surinamese, 215 Turkish, and 213 Moroccan origin participants of the HELIUS study (Amsterdam, the Netherlands). Logistic regression is used to determine the associations between plasma CEFA and T2D. Mediation analysis is used to identify whether CEFA contributed to the association between ethnicity and T2D. We adjusted for ethnicity, age, sex, smoking, physical activity, and BMI. Associations between plasma CEFA and T2D were similar across all ethnic groups. Although differences in plasma CEFA across ethnic groups were observed, CEFA did not mediate the differences in T2D prevalence between ethnic groups. Conclusion: Although ethnic differences in plasma CEFA are found and CEFA are associated with T2D, CEFA does not contribute to the difference in T2D prevalence between ethnic groups. If confirmed, this implies that maintenance of the more beneficial CEFA profiles in the non‐Dutch ethnic groups may be encouraged to prevent an even higher prevalence of T2D in these groups. Abstract : Ethnic minority groups in the Netherlands have a higher risk for type 2 diabetes than the host population. Differences in the amount and type of lipids in the diet and their metabolism may mediate ethnic differences in type 2 diabetes prevalence. It is found that plasma cholesteryl ester fatty acids are similarly associated with type 2 diabetes across ethnic groups. Therefore, cholesteryl ester fatty acids are important parameters to prevent type 2 diabetes across multiethnic groups. However, ethnic differences were not mediated by plasma cholesteryl ester fatty acids as these profiles were more beneficial in ethnic minority groups than in the Dutch ethnic group.